Design and implementation of cordic algorithm with sinusoidal pulse width modulation switching strategy - Madzzaini, Nur Sofea Eleena (2017)
Sinusoidal pulse width modulation (SPWM) is frequently used in motor control and inverter application. Sinusoidal wave in sinusoidal pulse width modulation (SPWM) is used to generate pulse width modulation (PWM) signal. Usually, one sinusoidal wave is used for one inverter. In this design, SPWM is used for multilevel inverter application in photovoltaic (PV) system. Generally, sinusoidal wave is generated using typical technique (unipolar sinusoidal pulse width modulation (SPWM) technique). For this technique, data is stored in Look Up Table (LUT). The size of required memory bits to store data in the LUT increases as the bit resolution of the generated digital sinusoidal wave increases. To overcome the large memory space, area and power consumption, CORDIC Algorithm is used to generate the sinusoidal wave. The SPWM controller will be designed using HDL Verilog codes and will be tested using MODELSIM for digital functionality. The SPWM controller will be implemented in VLSI ASIC flow. Coordinate Rotation, Digital Computer (CORDIC), known as Volders Algorithm based on its inventor, is an algorithm that is applied to perform trigonometric related computations. CORDIC is very popular for its potential of efficiency and low cost implementation of a large category of applications since it only requires shifter and adder. In addition, CORDIC algorithm has a low usage of memory space compared to Look Up table (LUT) technique. This design presents the uses of sinusoidal pulse width modulation (SPWM) as a switching control for multilevel inverter by using CORDIC algorithm. By the end of this project, it can be seen that the simulation is the same as the simulation of the previous project that have ever been done.